An "Outsider's" Perspective on Petr Vanicek's Approaches to Regional Geoid Determination - Featherstone, Will (Department of Geodesy and Geomatics Engineering, University of New Brunswick, 2003)
This paper overviews Petr Vancek's philosophies and approaches to regional geoid deter-mination that have been published in the open literature over the last three decades. This includes the formulation and application of the generalised Stokes scheme, mitigation of the truncation error through a deterministic kernel modification, and the determination of ap-propriate boundary values, including downward continuation, on the geoid.